2022
DOI: 10.2147/prom.s256715
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes in Rheumatoid Arthritis: A Key Consideration for Evaluating Biosimilar Uptake?

Abstract: Purpose This review aims to provide an overview of the impact of TNFis biosimilars, with marketing authorization, in patient-reported outcome measures (PROMs) scores and explore how PROMs endpoints might add value in biosimilars uptake in RA patients. Patients and Methods A comprehensive search of Medline, Scopus, Lilacs, and CINAHL databases was performed for papers published between January 2012 and December 2021. For inclusion, studies had to be prospective, publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…The systematic review and qualitative study conducted previously by our team [ 12 , 17 ] identified barriers and enablers to PROM implementation spanning all five CFIR domains, and 30 CFIR constructs. The systematic review and qualitative study had overlap in identifying barriers and enablers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review and qualitative study conducted previously by our team [ 12 , 17 ] identified barriers and enablers to PROM implementation spanning all five CFIR domains, and 30 CFIR constructs. The systematic review and qualitative study had overlap in identifying barriers and enablers.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these benefits, PROM uptake is limited, with some clinical areas reporting that 1% of clinicians use PROMs [15][16][17][18]. Many PROM implementation initiatives fail due to a lack of evidence-based implementation strategies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8,[13][14][15][16][17][18] Nonetheless, these recommendations have relied mainly on single trials or expert consensus, with only 2 guidelines using meta-analysis. 17,18 Previous systematic reviews [18][19][20][21][22][23][24][25][26][27][28][29] attempted to compile evidence on similar efficacy and safety between biosimilars and reference products for RA. Nonetheless, most of these reviews 18,19,21,23,24,27 provided only qualitative summaries, which are insufficient for decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Previous systematic reviews [18][19][20][21][22][23][24][25][26][27][28][29] attempted to compile evidence on similar efficacy and safety between biosimilars and reference products for RA. Nonetheless, most of these reviews 18,19,21,23,24,27 provided only qualitative summaries, which are insufficient for decision-making. The few reviews 20,22,25,26,28,29 that attempted quantitative analyses did not use appropriate equivalence testing methods, resulting in imprecise conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation